1989
DOI: 10.3164/jcbn.6.57
|View full text |Cite
|
Sign up to set email alerts
|

Use of K Value of Ascorbic Acid as a Clinical Index of Attack by Oxygen Radicals

Abstract: The K value = [AFR]2/[RAsA] [DAsA ] (RAsA, reduced form of ascorbic acid; DAsA, oxidized form of ascorbic acid; AFR, ascorbate free radical), and changes in AFR concentration in human serum were examined after exposure to oxygen radicals. After the exposure, RAsA decreased, DAsA increased, and K value increased. Since the K value is constant in healthy subjects, it is regarded to be a clinical index to indicate the attack of oxygen radicals in living system. Whereas changes in AFR concentration in ascorbate so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…In a study using the electron spin resonance (ESR) method, we previously found that OPZ increases in the ESR signal intensity of ascorbate radical (AFR) in vitro and that OPZ acts like oxygen radicals in altering the K value of ascorbic acid, which can be used as an index of free radical exposure in vivo [3,4]. Vitamin E exerts an anti-oxidant action by preventing the lipid peroxidation of unsaturated fatty acids in phospholipids containing peroxy radicals in biological cell membranes [5], and it also has a direct effect on oxygen radicals such as ringlet oxygen (102), superoxide (02-), and hydroxy radical • OH [6,7].…”
mentioning
confidence: 99%
“…In a study using the electron spin resonance (ESR) method, we previously found that OPZ increases in the ESR signal intensity of ascorbate radical (AFR) in vitro and that OPZ acts like oxygen radicals in altering the K value of ascorbic acid, which can be used as an index of free radical exposure in vivo [3,4]. Vitamin E exerts an anti-oxidant action by preventing the lipid peroxidation of unsaturated fatty acids in phospholipids containing peroxy radicals in biological cell membranes [5], and it also has a direct effect on oxygen radicals such as ringlet oxygen (102), superoxide (02-), and hydroxy radical • OH [6,7].…”
mentioning
confidence: 99%